The "Excelsior" H2020 Widespread Teaming Phase 2 Project: ERATOSTHENES: EXcellence Research Centre for Earth SurveiLlance and Space-Based MonItoring Of the EnviRonment - Hadjimitsis, Diofantos G.; Schreier, Gunter; Kontoes, Haris; Ansman, Albert; Komodromos, Giorgos; Themistocleous, Kyriacos; Neocleous, Kyriacos; Michaelides, Silas; Mamouri, Rodanthi-Elisavet; Papoutsis, Ioannis; Bühl, Johannes; Schwarz, Egbert; et al. (My University, 2020)
The EXCELSIOR project aims to upgrade the existing ERATOSTHENES Research Centre established within the Cyprus University of Technology into a sustainable, viable and autonomous ERATOSTHENES Centre of Excellence (ECoE) for Earth Surveillance and Space-Based Monitoring of the Environment. The ECoE for Earth Surveillance and Space-Based Monitoring of the Environment will provide the highest quality of related services both on the National, European and International levels through the ‘EXCELSIOR’ Project under H2020 WIDESPREAD TEAMING. The vision of the ECoE is to become a world-class Digital Innovation Hub (DIH) for Earth observation and Geospatial Information becoming the reference Centre in the Eastern Mediterranean, Middle East and North Africa (EMMENA) within the next 7 years. The ECoE will lead multidisciplinary Earth observation research towards a better understanding, monitoring and sustainable exploitation and protection of the physical, built and human environment, in line with International policy frameworks. Indeed, the scientific potential of the new upgraded ECoE focusing on the integration of novel Earth observation, space and ground based integrated technologies for the efficient systematic monitoring of the environment. Furthermore, ECoE aims to excel in five domains: i) Access to energy; ii) Disaster Risk Reduction; iii) Water Resource Management; iv) Climate Change Monitoring and v) Big Earth observation Data Analytics. This will be achieved through research and innovation excellence in the respective scientific and technological disciplines and working together with other Earth observation industries, whereby the ECoE will develop a pool of scientific expertise and engineering capability as well as technical facilities. The partners of the EXCELSIOR consortium include the Cyprus University of Technology as the Coordinator, the German Airspace Center (DLR), the Leibniz Institute for Tropospheric Research (TROPOS), the National Observatory of Athens (NOA) and the Department of Electronic Communications, of the Ministry of Transport, Communications and Works of Cyprus.